A fully tunable filter based on the improved tubular structure. Issue 4 (10th January 2022) - Zhang, Zhonghai; He, Yun; Gan, Li; Chen, Lin; Wu, Aiting; Zhang, Pengquan
Abstract: A fully tunable bandpass filter adopting a novel tubular type structure was presented in this letter. The fully tunable bandpass filter was mainly consisted of π type tunable resonators and coupling reactance. The π type tunable resonators were mainly consisted of step impedance lines and tunable capacitance. Adopting this scheme, the frequency and 3 dB bandwidth of the bandpass filter can all be tuned independently in certain range. This type of fully tunable bandpass filter has a better expansibility and can be easily designed to meet other performance in actual requirements.